An innovative coupling technique for integrating oil spill prediction model with finite volume method-based ocean model. (December 2022) - Liu, Darong; Mu, Lin; Ha, Si; Wang, Si; Zhao, Enjin
Abstract: Marine oil spill pollution have increased recent years, threatening the safety of the marine environment. This paper proposes a coupling technique: Fast Mapping & Addressing(FMA) that integrates the oil spill model with oceanographic model. The FMA technique is based on hash function and spatial quadtree algorithm to achieve efficient addressing from an unstructured to a structured grid. The oil spill model simulates the oil spill process, while the ocean model simulates the ocean currents. The efficiency is improved about ten times compared to the interpolation algorithm. Results reveal the difference between the simulation results of the ocean model and the measured data is minimal, with an MAE(Mean Absolute Error) and RMSE(Root Mean Square Error) of about 0.06 m. Moreover, two oil spill events in China's nearshore were selected to simulate and verify the results. Indeed, our model's results agree with the observed data, demonstrating that our model can achieve a satisfied simulation of oil spill. Highlights: The innovative coupling technique improves the efficiency of mapping and addressing. The simulation of ocean current from ocean model FVCOM is precise. Oil spill model coupling with FVCOM model simulate the crude oil spill full process. Two oil spill tracking and beaching results agree with the observed data and records.